Forgeries and historical writing in England, France, and Flanders, 900-1200 - Berkhofer III, Robert F. (Medieval Documentary Cultures Ser., 2022)
A close analysis of forgeries and historical writings at Saint Peter's, Ghent; Saint-Denis near Paris; and Christ Church, Canterbury, offering valuable access to why medieval people often rewrote their pasts.